Lying, Successful and False Metaphors for Chatbots’ Artificial Intelligence - Kreft, Jan; Cyrek, Barbara (Roczniki Kulturoznawcze, 2024)
Because the so-called artificial intelligence is becoming an integral part of large language models, personal assistants, or, for example, the so-called smart home, it is becoming increasingly important to know the factors of attitudes towards it and its tools. The observed dawn of new possibilities identified with artificial intelligence encourages us to better understand the metaphors used to describe it. Metaphors are not only the key to explaining the unknown, but also have significant heuristic value, are the foundation of modern rationality and can displace human judgment and minimize prejudices and critical reflection. The aim of the article is to identify metaphors and recognize their performative role in the discussion about artificial intelligence and its tools. The subject of the study are dominant metaphors appearing in the descriptions of media and new technologies and less known metaphors of chatbots present in journalistic texts, on the example of articles published in the opinion-forming The New York Times. As part of the study, we identify and analyze, among others, metaphors of „platform”, „network”, „mind as machine” and animate and inanimate metaphors accompanying artificial intelligence and its actors. We examine their persuasive nature and the goals of this persuasion.